Factors Limiting Legal Compliance in Managing Public Records: A Case of Business Registration and Licensing Agency (BRELA), Tanzania. - Kashaija, Lameck Sospeter; Ndumbaro, Faraja (University of Dar es Salaam Library Journal, 2021)
Legal compliance is one of the essential elements in the effective management of public records. The purpose of this paper is to assess factors limiting legal compliance in managing public records at Business Registration and Licensing Agency (BRELA) in Dar es Salaam, Tanzania. Specifically, the study aimed at finding the extent to which record practitioners at BRELA are aware of the existing records management legal frameworks; and determining factors limiting record practitioners in complying records management legal frameworks. A sample of 66 respondents was purposively recruited from a population of 88 BRELA staff members. Mixed method research design was employed, where by qualitative data were collected through interviews and observation while quantitative data were collected using questionnaires. The study revealed low level of awareness about records management legal frameworks among record practitioners. The results further suggest that BRELA has failed to make national legal frameworks available to records management staff members. Lack of legal compliance is contributed by lack of appropriate resources, low priority given to records management, out-dated legislations, and lack of guidance from President ' s Office Records and Archives Management Department (PO RAMD). The study recommends BRELA to ensure national records management legal frameworks are available to the record practitioners, to officially invite PO RAMD for inspecting records management practices and provide technical training and advice. Similarly, PO RAMD should regularly audit BRELA ' s records management practices and provide technical advice to enhance effectiveness.